Leveraging Dynamic Managerial Capabilities to Capitalize on Digital Transformation : An Exploratory Multiple Case Study Through the Lens of Dynamic Capabilities - Hess, Jelle (My University, 2022)
Digital transformation (DT) is a popular research theme in literature as well as an imperative for firms to withstand the increasing environmental turbulence. At the same time, it has been emphasized that DT remains a challenge. As DT is a source of change and disruption, linkages have been made with the organizational dynamic capabilities (DC) concept which help firms to address rapidly changing environments. This has led to the fit between DC as a conceptual foundation and DT as a phenomenon of interest. As a result, literature has been describing how organizational DC enable a firm to capitalize on DT. However, this does not provide the individual (i.e., managers) with ways for how to ensure the organizational DC are embedded in a firm. The dynamic managerial capabilities (DMC) concept was identified as a potential response to this issue. With this as motivation for writing this thesis, a multiple case study was set up to investigate the DMC phenomenon in more detail. By extensively examining prior literature on DT and DC, making the connection between the two concepts, and conducting two expert interviews, six in-depth interviews, and two validation interviews, this thesis gathered an amount of data which has been analyzed according to a within-case analysis and a cross-case analysis. As a result, a set of DMC are found that contribute to the development of organizational DC. This in turn enables a firm to integrate, build, and reconfigure competences, which enables a firm to capitalize on DT. Accordingly, this thesis provides managers with guidelines for how they could examine their current set of capabilities used for DT. Were applicable, they could adapt their current set of capabilities to the identified DMC in order to lead DT initiatives to success. Additionally, a conclusion is that managers should consider the factors underpinning the three underlying attributes, as this will actually ensure they are capable of performing the DMC appropriately. Concludingly, this thesis illustrates how to leverage DMC to capitalize on DT.
Keywords: digital transformation, dynamic capabilities, dynamic managerial capabilities